Acupuncture and herbal moxibustion for the treatment of 'BiQiu' (allergic rhinitis symptoms) in a Hong Kong Chinese medicine clinic: a randomized controlled trial - Ting Yiu Yung; Hongwei Zhang; Lap Che Tang; Lang Zhang; Chak On Law; Wai Man Tam; Chun Wai Chan; Heng Chun Chen; Man Hork Lee; Tat Chi Ziea; Fung Leung Ng; Zhi Xiu Lin (BMC, 2019)
Abstract Background Allergic rhinitis (AR) is a common disease. No evidence is available for the clinical application of acupuncture and moxibustion for the management of AR symptoms in Hong Kong. This study aimed to evaluate the clinical effectiveness of acupuncture with or without herbal moxibustion on relieving AR symptoms in the Hong Kong population. Methods A single-centre, randomized, assessor-blinded, controlled trial with three parallel arms (acupuncture alone, acupuncture combined with herbal moxibustion treatment and waitlist) was designed. Groups with acupuncture treatment received treatment 3 times per week for a total of 12 sessions in 4 weeks. Acupuncture combined with herbal moxibustion treatment group received herbal moxibustion once per week for a total of 4 sessions over 4 weeks in addition to acupuncture treatment. Participants in the waitlist group received no treatment. All patients received advice on healthy lifestyle, diet, and exercise. Results Ninety-six subjects were recruited and allocated randomly (1:1:1) into three study groups. Compared to the waitlist group, both treatment groups demonstrated statistically significant decreases in TNSS and RQLQ at the end of treatment as well as after follow-up period (all P < 0.01). However, there was no statistically differences between these two treatment groups. There was no difference in the change of total IgE levels among study groups before or after the treatment. Only one patient reported adverse effects with herbal moxibustion treatment, and no adverse effects were found in others. Conclusions This study supports that acupuncture could help relieve AR symptoms, but no evidence on additional treatment effect of herbal moxibustion was found. Trial registration ChiCTR-INR-16010047 registered on November 25, 2016.